War Politics: An Economic, Rational-Voter Framework - Hess, Gregory D.; Orphanides, Athanasios (American Economic Review, 1995)
The frequency of foreign conflict initiations in the United States is found to be significantly greater following the onset of recessions during a president's first term than in other periods. The authors develop an economic theory of the political use of wars which links the election cycle, war decisions, and economic performance consistent with the observed relationships among these events. An incumbent leader with an unfavorable economic performance record may initiate a war to force the learning of his war leadership abilities and thus salvage, with some probability, his reelection. This obtains despite voter rationality and informational symmetry. Copyright 1995 by American Economic Association.